(3edNU GdaQGFVs - (3GdGbSQGFj, MSf Hf YKeGf Hf MSGe GdOjfs ((3MSf Hf GdMSjf GdTGaYj GdeUQj GdUGhjs)
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg GdPj jQK GdCQV hef YdjgG jbhd MSf Hf YKeGf ef JdGejP HMQ GdYdhe hebHhd GdOjGf CafOj deG QCjJ GdhQi eGFdG Edi GdeNJUQGJ hQGZH Yf GdeWhdGJ CQOJ Cf CUfa eNJUQG aj Yde GdaQGFV hSejJg edNU GdaQGjVs
(3BNQgG (B:s
(3hbGd GHf eSYhO QVj Gddg YfgeG jQK HYVge ef HYV EdG eeG hQK cd hGMO efge ef eGd UGMHg dGfg dRe GdOhQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf (B2 / 1639s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
Keywords: (3GdaQGFVs